ESEM-EDS: AN IMPROVED TECHNIQUE FOR MAJOR ELEMENT CHEMICAL ANALYSIS OF FLUID INCLUSIONS - Timofeeff M.N.; Lowenstein T.K.; Blackburn W.H. (My University, 2000)
Quantitative chemical analyses of fluid inclusions in sedimentary and diagenetic minerals can greatly improve our understanding of the chemistry of ancient surface and near surface waters. The environmental scanning electron microscope (ESEM) with an attached X-ray energy dispersive system (EDS) is capable of producing rapid and accurate major element chemical analyses of individual fluid inclusions in crystals of halite greater than about 30 μm in diameter. The ESEM-EDS technique uses the same basic principles as the X-ray microanalysis of frozen fluid inclusions reported by Ayora and Fontarnau [Ayora, C., Fontarnau, R., 1990. X-ray microanalysis of frozen fluid inclusion. Chemical Geology, 89, pp. 135-148.] but operates in a low-vacuum environment, which allows direct observation of the fluid inclusions to be analyzed without the need for a conductive coating. Modifications of the technique of Ayora and Fontarnau [Ayora, C., Fontarnau, R., 1990. X-ray microanalysis of frozen fluid inclusion. Chemical Geology, 89, pp. 135-148.] also include a newly designed sample holder, modified methods for the preparation of standard brine solutions to obtain ''glass-like'' homogeneous freezing behavior by addition of ethylene glycol, and a technique to obtain flat smooth surfaces on standard brine solutions. The ability to observe samples before analysis led to the discovery of heterogeneous freezing behavior of some standard solutions and fluid inclusions, which adversely influenced measurement reproducibility. The ESEM-EDS technique yielded quantitative results for Ca, Mg, K, SO4, and Cl at concentrations above about 0.1 wt.%; for Na, quantitative analyses were achieved at concentrations above 0.5 wt.%. Accuracies for the major elements in aqueous standards were better than 7% and precisions (relative standard deviations) ranged from 2% to 7%. Results on fluid inclusions in laboratory-grown halite gave accuracies of 6% to 10% for Mg, Ca, and K and precisions from 3% to 16%.
Keywords: FLUID INCLUSIONS; X-RAY MICROANALYSIS; ENVIRONMENTAL SCANNING ELECTRON MICROSCOPE (ESEM)